Catalytic asymmetric [2+2] cycloaddition between quinones and fulvenes and a subsequent stereoselective isomerization to 2, 3-dihydrobenzofurans. Issue 49 (5th June 2017) - Zheng, Haifeng; Xu, Chaoran; Wang, Yan; Kang, Tengfei; Liu, Xiaohua; Lin, Lili; Feng, Xiaoming
Abstract : A chiral Lewis acid catalyzed enantioselective [2+2] cycloaddition between quinones and fulvenes was reported for the first time. The method afforded a series of [6, 4, 5]-tricyclic cyclobutane derivatives in good yields with excellent regio- and stereoselectivities. Furthermore, the [2+2] adducts could be easily converted into formal [3+2] adducts efficiently and stereoselectively. Abstract : The catalytic enantioselective [2+2] cycloaddition between quinones and fulvenes was achieved, for the first time, by the use of a chiral copper(ii ) complex catalyst. The transformation afforded a series of enantiomerically enriched [6, 4, 5]-tricyclic cyclobutane derivatives in good yields with excellent regio- and stereoselectivities. Furthermore, the [2+2] adducts could be easily converted into formal [3+2] adducts efficiently and stereoselectively.